2017
DOI: 10.1136/flgastro-2017-100839
|View full text |Cite
|
Sign up to set email alerts
|

Establishing an anaesthetist-delivered propofol sedation service for advanced endoscopic procedures: implementing the RCA/BSG guidelines

Abstract: These guidelines facilitated a propofol sedation service with considerable benefits for patients and endoscopists. Provision of deep propofol sedation by an anaesthetist, in patients with an unsecured airway, appears practical, effective and efficient. Small adjustments to the airway were fairly common, but the incidence of adverse events and requirement for airway instrumentation was low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…7 As a result, guidelines introduced by major anesthesia societies have recommended that propofol be used only by anesthesiologists, alongside constant monitoring and preparation for urgent endotracheal intubation. 8 Etomidate may be an appropriate hypnotic agent for colonoscopy, especially for elderly patients, because of its relatively rapid onset and recovery and minimal adverse effects on the cardiovascular system owing to its lack of inhibitory effect on sympathetic tone and myocardial function. 9 A previous study reported that histamine release and allergic reactions to etomidate are less common than to barbiturates or propofol.…”
Section: Introductionmentioning
confidence: 99%
“…7 As a result, guidelines introduced by major anesthesia societies have recommended that propofol be used only by anesthesiologists, alongside constant monitoring and preparation for urgent endotracheal intubation. 8 Etomidate may be an appropriate hypnotic agent for colonoscopy, especially for elderly patients, because of its relatively rapid onset and recovery and minimal adverse effects on the cardiovascular system owing to its lack of inhibitory effect on sympathetic tone and myocardial function. 9 A previous study reported that histamine release and allergic reactions to etomidate are less common than to barbiturates or propofol.…”
Section: Introductionmentioning
confidence: 99%
“…If this happens when the sedation provider is not trained in airway management, there can be many adverse events, which are sometimes dangerous for patients [4]. Propofol is a short-acting intravenous anaesthetic agent and has been shown to provide better sedation and recovery quality, improve patient and endoscopist satisfaction, and the overall outcome of the procedural sedation compared to standard conscious sedation [8,9]. However, the use of propofol has been extensively debated.…”
Section: Safety Of Sedation In Advanced Endoscopic Proceduresmentioning
confidence: 99%
“…Propofol is a short-acting intravenous anaesthetic agent and has been shown to provide better sedation and recovery quality, improve patient and endoscopist satisfaction, and the overall outcome of the procedural sedation compared to standard conscious sedation [ 8 , 9 ]. However, the use of propofol has been extensively debated.…”
Section: Safety Of Sedation In Advanced Endoscopic Proceduresmentioning
confidence: 99%
“…Propofol sedation for complex endoscopy procedures is recommended by expert bodies, but the requirements of service provision often limit its availability. Smith and colleagues6 present a retrospective audit on the use of propofol sedation and report safety, tolerability and efficacy outcomes. What remains to be addressed are the governance issues of resources allocation and training competence when considering such deep sedation vs intubated general anaesthesia.…”
Section: Deep Sedation Versus General Anaesthesia In the Endoscopy Unitmentioning
confidence: 99%